Women Ridesharing Drivers’ Responses to Sexual Violence on the Job: The Role of Confrontation - Crowley, Jocelyn Elise (Journal of interpersonal violence, 2025)
One critical area where sexual violence has been underexplored is in the ridesharing industry in the United States, where women drivers frequently must interact with unknown male passengers. Sexual violence against them is categorized as technology-facilitated gender-based violence in the online to offline world, where services such as transportation are ordered through an online app and result in a person-to-person interaction once the driver picks the passenger up. Since ridesharing drivers are mostly independent contractors, they do not have at their disposal traditional legal and strong organizational remedies to address sexual violence; moreover, like all victims of violence, these methods usually can only be accessed after the incident has taken place. Instead, in the moment of sexual violence, they must often utilize informal methods at their disposal, including confrontational and nonconfrontational coping tools. This study uses qualitative content analysis methods on a survey of 32 ridesharing drivers (31 women and 1 nonbinary individual) who described 69 cases of sexual violence. It found that confrontational responses dominated, including the following: verbal opposition sometimes paired with physicality; canceling the ride, threatening to stop the ride, and actually stopping the ride; and threatening to attack the perpetrator, actually attacking the perpetrator, and threatening to involve the police. Less common nonconfrontational responses included emotional reactions; other strategies in this category involved ignoring the perpetrator, joking with the perpetrator, and changing the conversational subject. This study has important implications for understanding the contextual environment where confrontation is prevalent and strongly points to additional needed safeguards for drivers, passenger education campaigns, as well as app-based transportation corporate reform.